The Effect of Jump to Box Training towards Triple Jump Ability at SMA Negeri 2 Bungo - Dwiwinanda, Prandi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research is a quantitative research with experimental method with the research design used is